ChemInform Abstract: Diversity‐Oriented Approach to Natural Product Inspired Pyrano‐Carbazole Derivatives: Strategic Utilization of Hetero‐Diels—Alder Reaction, Fischer Indolization and the Suzuki—Miyaura Cross‐Coupling Reaction. Issue 10 (February 2016) - Kotha, Sambasivarao; Ali, Rashid; Saifuddin, Mohammad
Abstract: Starting from 1, 3‐diones, styrene derivatives, and formaldehyde the three‐step title sequence provides architecturally complex pyrano‐carbazole derivatives without the requirement of lengthy protective group strategies.